A hierarchical typology of multimodal scientific writing in early primary grades - Nichols, Deborah L.; Neal, Ted; Hand, Brian (Frontiers in Communication, 2025)
IntroductionScientific literacy in early education depends on both content knowledge and young learners' ability to organize and express scientific ideas across linguistic and visual-graphical modes. This integrative ability, known as multimodal competency, enables children to construct and communicate scientific understanding by coordinating text structure, language, and visual representation.MethodsIn this study, 1,705 science writing samples from 1,008 students in kindergarten through 2nd grade were analyzed using a two-stage quantitative approach. First, a content analysis was conducted in which each sample was systematically coded for text structure, linguistic and visual-graphical modes, and scientific content. These coded features were then subjected to latent class analysis (LCA) to identify distinct typologies of multimodal text production.ResultsLCA identified six typologies of multimodal composition, ranging from simple unlabeled visual texts to strategically integrated complementary compositions. These typologies capture meaningful variation in how students organize and communicate scientific ideas, reflecting differences in metacognitive strategy use, modality coordination, and sensitivity to the communicative functions of linguistic and visual modes.DiscussionFindings indicate that young children's multimodal texts act as both communicative and epistemic tools, supporting scientific meaning-making. Rather than requiring explicit instruction, just-in-time scaffolds may help children make strategic representational choices, reinforcing the role of multimodal composition in early science learning.